The effect of variable operating parameters for hydrocarbon fuel formation from CO2 by molten salts electrolysis. Issue 40 (September 2020) - Al-Juboori, Ossama; Sher, Farooq; Hazafa, Abu; Khan, Muhammad Kashif; Chen, George Z.
Graphical abstract: Highlights: A study of carbon dioxide capture and conversion into hydrocarbon fuels in molten carbonate and hydroxide salts is performed. The contribution of estimated temperature, applied voltage, and feed gas composition is crucial for hydrocarbons formation. The hydrocarbon fuel like methane was predominantly and experimentally produced during co-electrolysis of CO2 /H2 O. The current efficiency of 99.5% was achieved for H2 in molten hydroxide (LiOH–NaOH; 27:73 mol%) at 2 V and 275 ℃. The molten salts are suggested as a viable option for hydrocarbon fuel production without utilization any catalyst. Abstract: The emission of CO2 has been increasing day by day by growing world population, which resulted in the atmospheric and environmental destruction. Conventionally different strategies, including nuclear power and geothermal energy have been adopted to convert atmospheric CO2 to hydrocarbon fuels. However, these methods are very complicated due to large amount of radioactive waste from the reprocessing plant. The present study investigated the effect of various parameters like temperature (200–500 °C), applied voltage (1.5–3.0 V), and feed gas (CO2 /H2 O) composition of 1, 9.2, and 15.6 in hydrocarbon fuel formation in molten carbonate (Li2 CO3 –Na2 CO3 –K2 CO3 ; 43.5:31.5:25 mol%) and hydroxide (LiOH–NaOH; 27:73 and KOH–NaOH; 50:50 mol%) salts. The GC results reported that CH4 was the predominant hydrocarbon product with a lower CO2 /H2 O ratio (9.2) at 275 °C under 3 V in molten hydroxide (LiOH–NaOH). The results also showed that by increasing electrolysis temperature from 425 to 500 °C, the number of carbon atoms in hydrocarbon species rose to 7 (C7 H16 ) with a production rate of 1.5 μmol/h cm 2 at CO2 /H2 O ratio of 9.2. Moreover, the electrolysis to produce hydrocarbons in molten carbonates was more feasible at 1.5 V than 2 V due to the prospective carbon formation. While in molten hydroxide, the CH4 production rate (0.80–20.40 μmol/h cm 2 ) increased by increasing the applied voltage from 2.0–3.0 V despite the reduced current efficiencies (2.30 to 0.05%). The maximum current efficiency (99.5%) was achieved for H2 as a by-product in molten hydroxide (LiOH–NaOH; 27:73 mol%) at 275 °C, under 2 V and CO2 /H2 O ratio of 1. Resultantly, the practice of molten salts could be a promising and encouraging technology for further fundamental investigation for hydrocarbon fuel formation due to its fast-electrolytic conversion rate and no utilization of catalyst.